Oligomannurarate sulfate inhibits CXCL12/SDF-1-mediated proliferation and invasion of human tumor cells in vitro - Wen Wei-wei; Xie Shao; Xin Xian-liang; Geng Mei-yu; Ding Jian; Chen Yi (Acta Pharmacologica Sinica, 2016)
Aim: JG6 is a novel marine-derived oligosaccharide that has shown to inhibit angiogenesis and tumor metastasis. In this study, we sought to identify the potential target responsible for the anti-cancer activity of JG6. Methods: Human liver cancer cell line Bel-7402 and human cervical cancer cell line HeLa were examined. CXCL12-stimulated cell proliferation and migration were determined using a CCK-8 kit and a transwell assay, respectively. Western blotting was performed to examine the changes in CXCL12/CXCR4 axis. Molecular docking and surface plasmon resonance (SPR) were performed to characterize the possible interaction between JG6 and the CXCL12/CXCR4 axis. Results: Treatment with CXCL12 potently stimulated the proliferation and migration in both Bel-7402 and HeLa cells. Co-treatment of the cells with JG6 (10, 50 and 100 μg/mL) dose-dependently impeded the CXCL12-stimulated cell proliferation and migration. Furthermore, CXCL12 rapidly induced phosphorylation of AKT, ERK, FAK and Paxillin in Bel-7402 and HeLa cells, whereas pretreatment with JG6 dose-dependently inhibited the CXCL12-induced phosphorylation of these proteins. The SPR assay showed that JG6 bound to CXCL12 with a high affinity. In molecular docking study, JG6 appeared to interact with CXCL12 via multiple polar interactions, including 6 ionic bonds and 7 hydrogen bonds. Conclusion: Inhibition of the CXCL12/CXCR4 axis by JG6 may account for its anticancer activity.